Natural history of the West Indies - Fernández de Oviedo y Valdés, Gonzalo, 1478-1557 (North Carolina studies in the Romance languages and literatures, 2018)
Where the only previous translations of Gonzalo Fernandez de Oviedo's Natural History of the West Indies (1555 and 1625) are now unreadable, Sterling A. Stoudemire's translated edition offers this foundational text to the modern reader in an accessible format. The original text, published in 1525, is a beautiful Gothic example of the early Spanish-American chronicle, and is of great rarity. It offers the eyewitness account of a true historian and naturalist, and is the source of some of Europe's first descriptions of the flora and fauna of the Americas. Stoudemire offers comprehensive introductory material on the author of the text and its writing, drawing not only on the original text, but the excellent work of Enrique Alvarez Lopez, a naturalist who has published excellent versions of the Natural History in modern Spanish. This leads Stoudemire's English version to be a beautiful rendition that is both accurate and readable. It presents the heart of Oviedo's work without the interminable unpunctuated sentences of the original, and as such is an excellent introduction to both the Chronicle as a genre, and to Oviedo's oeuvre.